Analysis of amplang processing business UD. Taufik Jaya Makmur in Sidomulyo Village Samarinda Ilir Sub-District, Samarinda City - Novianti, Rina; Helminuddin , Helminuddin; Fahrizal, Wahyu (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
This study aims to determine the cost and profit of amplang processing business and determine the feasibility of amplang processing business. This research uses saturated sampling method or census. Data analysis using cost analysis and business feasibility analysis.  Based  on the  results of the  analysis  of costs  incurred amounted to Rp 100.696.857 / month, profit of Rp 139.303.143 / month, R / C value of 2.38, payback period 1.16 month.